Sistem Bantu IMPLEMENTASI GEOFENCING UNTUK SISTEM PRESENSI KARYAWAN DARI LUAR KANTOR PADA BADAN PERTANAHAN KAB. NGANJUK: Rekayasa Perangkat Linak - Fitriyana, Wahyu Tia; Patmi Kasih; Danar Putra Pamungkas (Universitas Nusantara PGRI Kediri, 2025)
In today's digital era, efficient employee attendance management remains a crucial challenge for organizations, especially those with staff who work remotely or in different locations. This study overcomes the inefficiency of the manual attendance process at the Nganjuk Regency National Land Agency (BPN) through the development of an Android-based attendance application. By utilizing geofencing technology, this system increases data accuracy, efficiency and security. This research uses the waterfall method to adopt a systematic approach. The research results, in the form of attendance to verify employee locations, show the potential of technology-based solutions in increasing organizational productivity.